PYRITE FORMATION BY REACTIONS OF IRON MONOSULFIDES WITH DISSOLVED INORGANIC AND ORGANIC SULFUR SPECIES - Wilkin R.T.; Barnes H.L. (My University, 1996)
Pyrite formation has been investigated at 70°C and pH 6-8 by aging precipitated, disordered mackinawite, Fe9S8, and greigite, Fe3S4, in solutions containing aqueous H2S, HS-, S2-x, S2O2-3, SO2-3, colloidal elemental sulfur, and the organic sulfur species thiol, disulfide, and sulfonate. Pyrite formed in all experiments where unoxidized iron monosulfides were aged with species containing zero-valent sulfur, i.e., polysulfides and colloidal elemental sulfur, but not with hydrogen sulfide (or bisulfide), the sulfoxy anions, or the organic sulfur species. Pyrite formation also occurred in experiments where the starting monosulfides were air-exposed prior to aging in sulfide solutions, or when air was bubbled through a reaction vessel containing iron monosulfides suspended in a sulfide solution. The experiments indicate the rate of conversion from iron monosulfides to pyrite is not only a function of solution chemistry (i.e., pH and aqueous speciation), but also depends on the surface oxidation state of the precursor iron monosulfides.Measurements of δ34S of reactants and products from pyrite-forming experiments suggest that the conversion from iron monosulfides to pyrite may proceed via loss of ferrous iron from, rather than via addition of zero-valent sulfur to, the precursor monosulfides. The sulfur isotopic composition of pyrite in sedimentary environments should reflect the sulfur isotopic composition of the precursor iron monosulfide plus sulfur sources incorporated during surface-controlled growth processes.Pyrite forms produced in this study ranged from poorly developed octahedral grains, in experiments where initial pyritization rates were the slowest, to framboidal aggregates in experiments where initial pyritization rates were the fastest. Although greigite formation occurred in experiments that produced framboids, not all experiments that produced greigite led to framboid formation. The formation of pyrite with framboidal texture is apparently favored when iron monosulfides rapidly convert to pyrite.